Behavioral Assumptions of Management Accounting. - Caplan, Edwin H. (The Accounting Review, 1966)
Accounting is closely associated with the development of the modern business organization. Thus, accountants are expected to show a strong interest in recent contributions to organization theory which increases the understanding of the business firm and how it functions. However, an examination of accounting literature suggests that accountants have been relatively unconcerned with current research in organization theory. Although the past few years have witnessed the beginnings of an effort to bridge this gap, much still remains to be done. This article attempts to demonstrate that an understanding of behavioral theory is relevant to the development of management accounting theory and practice. The management of a business enterprise is faced with an environment–both internal and external to the firm–that is in a perpetual state of change. Not only is this environment constantly changing, but it is changing in many dimensions. These include physical changes, technological changes, social changes and financial changes. An important characteristic of good management is the ability to evaluate past changes, to react to current changes and to predict future changes.